Distinct plasma gradients of microRNA-204 in the pulmonary circulation of patients suffering from WHO Groups I and II pulmonary hypertension. (March 2019) - Estephan, Leonard E.; Genuardi, Michael V.; Kosanovich, Chad M.; Risbano, Michael G.; Zhang, Yingze; Petro, Nancy; Watson, Annie; Al Aaraj, Yassmin; Sembrat, John C.; Rojas, Mauricio; Goncharov, Dmitry A.; Simon, Marc A.; et al.
Pulmonary hypertension (PH), a heterogeneous vascular disease, consists of subtypes with overlapping clinical phenotypes. MicroRNAs, small non-coding RNAs that negatively regulate gene expression, have emerged as regulators of PH pathogenesis. The muscle-specific micro RNA (miR)-204 is known to be depleted in diseased pulmonary artery smooth muscle cells (PASMCs), furthering proliferation and promoting PH. Alterations of circulating plasma miR-204 across the trans-pulmonary vascular bed might provide mechanistic insights into the observed intracellular depletion and may help distinguish PH subtypes. MiR-204 levels were quantified at sequential pulmonary vasculature sites in 91 patients with World Health Organization (WHO) Group I pulmonary arterial hypertension (PAH) (n = 47), Group II PH (n = 22), or no PH (n = 22). Blood from the right atrium/superior vena cava, pulmonary artery, and pulmonary capillary wedge was collected. Peripheral blood mononuclear cells (PBMCs) were isolated (n = 5/group). Excretion of miR-204 by PAH-PASMCs was also quantified in vitro. In Group I patients only, miR-204 concentration increased sequentially along the pulmonary vasculature (log fold-change slope = 0.22 [95% CI = 0.06–0.37], P = 0.008). PBMCs revealed insignificant miR-204 variations among PH groups ( P = 0.12). Cultured PAH-PAMSCs displayed a decrease of intracellular miR-204 ( P = 0.0004), and a converse increase of extracellular miR-204 ( P = 0.0018) versus control. The stepwise elevation of circulating miR-204 across the pulmonary vasculature in Group I, but not Group II, PH indicates differences in muscle-specific pathobiology between subtypes. Considering the known importance of miR-204 in PH, these findings may suggest pathologic excretion of miR-204 in Group I PAH by PASMCs, thereby accounting for decreased intracellular miR-204 concentration.